Where Is the Son of Man Coming or Going?: Daniel 7:13–14’s Place in Jesus’s Eschatology - MacPherson, Anthony J. (The Evangelical quarterly, 2024)
In Daniel 7 the ‘Son of Man coming with the clouds’ appears to move toward (or within) heaven. In the apocalyptic discourses Jesus has the Son of Man moving in the opposite direction to earth, traditionally understood as the Second Coming. Resolutions of the discrepancy include arguing that Daniel 7 refers to Jesus’s ascension, that the Synoptics use Daniel’s language to refer to a coming in judgement against Jerusalem in A.D. 70, others suggest evolutionary developments in the early church or a mistaken Jesus. This article suggests Jesus’s use of Daniel reflects a close exegetical reading of the text. There is no discrepancy.